A energia fotovoltaica num contexto CTSA: uma sequência de ensino sobre as transformações de energia solar em energia elétrica - Carlos Eduardo Lima (2018)
This dissertation is part of the compulsory requirement to obtain the Master's Degree in Education and Teaching, in the line of research in Science Teaching, by the Professional Master's Education and Teaching of FaE / UFMG. It presents the results of the research developed entitled "Photovoltaic Energy in a CTSA context: a Teaching Sequence on Solar Energy Transformations in Electrical Energy". In the research was developed and applied a sequence of teaching (SE), in Physics, whose title was "Transformations of Solar Energy in Electric Energy", for students of the 3rd year of high school in a state public school in the city of Belo Horizon. The SE has a teaching structure focused on Science, Technology, Society and Environment (CTSA), based on activities, with some investigative characteristics, counting on the use of diverse mediational resources such as videos, texts, flowcharts, maps, simulators, among others, besides a technological artifact: a mini solar photovoltaic. After the application of the SE, we sought to analyze the interviews made with some of its subjects (students, teacher and scholars PIBID / Physics) and the written answers of the students, in the resolution of the activities of the SE. In our analysis, we sought to highlight possible limits and potentialities of the sequence for students' physical concepts learning and their possible contribution in the formation of more critical and reflexive citizens (active in society and the environment) on the subject of photovoltaic solar energy. In our analysis we use James V. Wertsch's Theory of Mediated Action (TAM) and Aguiar and Ozella's Discourse Meaning Nuclei. Based on our analysis, we reworked the SE that will be available, along with some pedagogical guidelines, for physics and science teachers in basic education.